Concepções de ensino aprendizagem de matemática e os projetos pedagógicos no ensino médio inovador - Périgo, Irene Célia Bianchini (2017)
This work presents an investigation about the conceptions of teaching and learning Mathematics in relation to the projects developed in a State School of High School, which participates in the Higher Education and Innovation Program (ProEMI). The Program aims to innovate the methodologies used within the school context attending the Secondary Schools in the country. This study seeks to answer the research question: What conceptions of teaching Mathematics are present in the pedagogical projects performed in the Innovative Higher Education Program, according to the speaches and practices of those who elaborate and develop them. According the objectives of the study, we opted for a qualitative approach, in which the analysis of the information produced is presented in an interpretive way. The study was based on three Mathematics’ teachers and the articulator of the High School Innovation Program, from a Public School, in Nobres - Mato Grosso. The research occurred from March to May 2016. Informations were poduced through notes practices developed in the projects, questionnaires, semi-structured interviews with the research participants and documentary analysis. The theoretical referential that guided this research was organized to give support to the understanding conceptions of Mathematics teachers, in relation to their practices in the projects, a theoretical contribution was looked for in Becker (1993), Darsie (1999), D'Ambrosio (1996) ), Fiorentini (1995), Fiorentini and Lorenzato (2009), Ponte (1992), Ponte, Brocardo & Oliveira (2009), among others. In way of the discussion about projects and high school, the dialogue was with authors such as Prado (2003), Nogueira (2001, 2012), Antunes (2015), Krawczyk (2011), Kuenzer (1997, 2002), among others. In documentary analysis, elements were observed in project planning within the Pedagogical Action Plan and the School's Political Pedagogical Project (PPP). The interpretation of the datas occurred through the search of manifested conceptions into their practices and speeches and also the traditional and constructivist epistemological implications present in these conceptions. As a result, it was observed that, in the conceptions about learning and teaching of teachers, there is a mismatch between the active conceptions and the conceptions manifested by the participants of the research. Perhaps imperceptible to them that point to a constructivist conception although we still observes an alternation with the traditional conception, that stays strong in its practices, discordant of its speeches. Regarding Mathematics teaching, the actions developed in the projects converge towradsa possible improvement the quality of teaching offered by this area of knowledge. This research, carried out with teachers of the Innovative High School, demonstrates the importance of the changes of conceptions from the reflection of the pedagogical practices.